Association between religious practice and healthy lifestyle in students from Pelotas, RS, Southern Brazil - Cabistany, Léo Dutra; Rombaldi, Airton José (ABCS Health Sciences, 2014)
Introduction: Among the approaches that can positively influence the adoption and maintenance of healthy habits, the religious practice or the influence of religion seems to be important due to the adoption of ethical principles. Objective: This study aimed at evaluating the potential association between religious practice and healthy lifestyle among adolescents attending the last year of high school from two public schools in Pelotas, Rio Grande do Sul, Brazil. Methods: Cross-sectional study with a convenience sample of 183 students, aged at least 15 years old, including boys and girls. The students answered a self-administered instrument containing 118 questions; the outcomes were related to religious practice. Result: There was a borderline association between the age of sexual initiation and frequency to religious cults (p=0.05). Moreover, the study showed significant associations between having received religious instruction and drinking alcohol in the last 30 days (p=0.03); and between watching TV for more than 2 hours and being engaged in religious practice for more than 10 years (p=0.04). Conclusion: The study found different associations between religious practice and its dependent variables. This area of study should be more thoroughly investigated in larger, representative samples, so that we can provide more objective evidence about religious practice and its potential influence on the physical health of individuals who profess every sort of religious belief.